2011
DOI: 10.2474/trol.6.219
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Soap Fiber Structure on Boundary Lubrication of Lithium Soap Greases

Abstract: This paper describes the influence of fiber length of lithium-soap thickener of greases on friction under boundary lubrication conditions. Ball-on-disk sliding tests were conducted with lithium soap greases with polyol ester as the base oil. The tests revealed that the greases had a lower friction coefficient than that for the base oil. The grease with a long soap fiber structure had a lower friction coefficient than that for the grease with a short soap fiber structure. The tests with only soap fibers showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…Grease-A can form thicker film, because film thickness of G-I base oil is thicker than that of G-IV base oil. In addition, Li-complex thickener raises film thickness more, since the thin and long fiber structure can enter the contact area as Yokouchi et al reported [10]. The thickener behavior also increases grease abundance in the inlet of EHL contact area.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Grease-A can form thicker film, because film thickness of G-I base oil is thicker than that of G-IV base oil. In addition, Li-complex thickener raises film thickness more, since the thin and long fiber structure can enter the contact area as Yokouchi et al reported [10]. The thickener behavior also increases grease abundance in the inlet of EHL contact area.…”
Section: Discussionmentioning
confidence: 81%
“…In contrast, the fiber structure of Grease-B exhibited thicker feature so that the thickener accumulated in the inlet region of contact area, which must have led to oil starvation. Yokouchi et al reported similar ideas that the grease with longer soap fibers had a higher capability to be entrained into the conjunction, although it was referred in boundary lubrication [10]. Based on these factors, lubrication mechanisms in this study are proposed as shown in Figs.…”
Section: Discussionmentioning
confidence: 85%
“…Kimura et al [14] controlled the thickness of the thickener fibers through the optimization of the heating-cooling conditions in its manufacturing process. Yokouchi et al [15] and Oikawa et al [16] studied the effect of fiber length, and showed that the grease with longer soap fibers was more easily entrained into the contact and showed favorable lubrication with low friction coefficient. All these works suggest that the role of thickener in grease lubrication should not be neglected.…”
Section: Introductionmentioning
confidence: 99%
“…The ratio may depend on physical property of the grease, the parameter of the bearing and an operating condition. The yield stress Y represents the physical property of the grease, and the coefficient 9.6 of equation (4) corresponds to the parameter of the bearing and an operating condition. A physical meaning of equation (4) may be as follows; the yield stress Y represents the ability to channel in the allowed space and the coefficient 9.6 represents the possible space for grease to channel between balls and races.…”
Section: Bearing Torque Characteristicsmentioning
confidence: 99%